An Image Processing Protocol to Extract Variables Predictive of Human Embryo Fitness for Assisted Reproduction - Chéles, Dóris Spinosa [UNESP]; Ferreira, André Satoshi [UNESP]; de Jesus, Isabela Sueitt [UNESP]; Fernandez, Eleonora Inácio [UNESP]; Pinheiro, Gabriel Martins [UNESP]; Dal Molin, Eloiza Adriane [UNESP]; Alves, Wallace [UNESP]; de Souza, Rebeca Colauto Milanezi [UNESP]; Bori, Lorena; Meseguer, Marcos; Rocha, José Celso [UNESP]; Nogueira, Marcelo Fábio Gouveia [UNESP] (MDPI, 2022)
Despite the use of new techniques on embryo selection and the presence of equipment on the market, such as EmbryoScope® and Geri®, which help in the evaluation of embryo quality, there is still a subjectivity between the embryologist’s classifications, which are subjected to interand intra-observer variability, therefore compromising the successful implantation of the embryo. Nonetheless, with the acquisition of images through the time-lapse system, it is possible to perform digital processing of these images, providing a better analysis of the embryo, in addition to enabling the automatic analysis of a large volume of information. An image processing protocol was developed using well-established techniques to segment the image of blastocysts and extract variables of interest. A total of 33 variables were automatically generated by digital image processing, each one representing a different aspect of the embryo and describing a different characteristic of the blastocyst. These variables can be categorized into texture, gray-level average, gray-level standard deviation, modal value, relations, and light level. The automated and directed steps of the proposed processing protocol exclude spurious results, except when image quality (e.g., focus) prevents correct segmentation. The image processing protocol can segment human blastocyst images and automatically extract 33 variables that describe quantitative aspects of the blastocyst’s regions, with potential utility in embryo selection for assisted reproductive technology (ART).
Keywords: blastocyst; digital image processing; embryo selection; morphology-derived variables; segmentation